2015
DOI: 10.1007/s10726-015-9441-y
|View full text |Cite
|
Sign up to set email alerts
|

Concessions Dynamics in Electronic Negotiations: A Cross-Lagged Regression Analysis

Abstract: We analyze concession patterns in electronic negotiations using a modified version of the Actor-Partner Interdependence Model (APIM). Our extension of the APIM takes into account that concessions in negotiations can only be evaluated in terms of utilities of the receiving side. We show that actor and partner effects in that model can directly be related to central concepts of negotiation theory such as cooperative versus distributive bargaining tactics and reciprocity. Based on this connection, we formulate hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Previous work on determining behavioural negotiation patterns (Pesendorfer et al 2007;Sokolova et al 2004) identified indicators for strategic orientations, concession behaviour, information disclosure, emotions etc. (McGinn et al 2003;Van Kleef et al 2004;Vetschera 2016). These individual behavioural components can collectively provide key cues for particular strategic and behavioural orientations through a systematic linkage ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work on determining behavioural negotiation patterns (Pesendorfer et al 2007;Sokolova et al 2004) identified indicators for strategic orientations, concession behaviour, information disclosure, emotions etc. (McGinn et al 2003;Van Kleef et al 2004;Vetschera 2016). These individual behavioural components can collectively provide key cues for particular strategic and behavioural orientations through a systematic linkage ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work on determining behavioural negotiation patterns (Pesendorfer et al 2007;Sokolova et al 2004) identified indicators for strategic orientations, concession behaviour, information disclosure, emotions etc. (McGinn et al 2003;Van Kleef et al 2004;Vetschera 2016). These individual behavioural components can collectively provide key cues for particular strategic and behavioural orientations through a systematic linkage ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in analyzing substantive behavior like concessions using an APIM model, one has to take into account that each side evaluates behavior according to its own preferences. These difference in evaluation require an even more complex model than the original APIM (Vetschera 2016).…”
Section: Generic Approachesmentioning
confidence: 99%